2015
DOI: 10.1016/j.jaip.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Children and Adults With Frequent Hospitalizations for Asthma Exacerbation, 2012-2013: A Multicenter Observational Study

Abstract: The present work focuses on neutronics analysis for the disposal of damaged fuels from Fukushima nuclear power plants. MCNP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Participants in the focus group affirmed and validated each other’s frustration related to accessing providers who may prescribe and refill medications, which in turn left them relying on the ED for prescriptions. This increased healthcare utilization contributes to the significant expenditures on asthma and inadequate guideline-based asthma care [26] and is reflective of barriers to timely telephone or office visit access to providers.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the focus group affirmed and validated each other’s frustration related to accessing providers who may prescribe and refill medications, which in turn left them relying on the ED for prescriptions. This increased healthcare utilization contributes to the significant expenditures on asthma and inadequate guideline-based asthma care [26] and is reflective of barriers to timely telephone or office visit access to providers.…”
Section: Discussionmentioning
confidence: 99%
“…The study design, setting, participants, and measured variables have been reported previously [13,14]. Briefly, we used a primary discharge diagnosis of Abbreviations: CI, confidence interval; IQR, interquartile range; MARC, Multicenter Airway Research Collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, NIV was used frequently in PICU patients, 66.6% versus the 3% reported in an American study and the 36% reported in a Saudi study. 1,11,12 Despite the potential beneficial effects attributed to NIV, there is no consensus in the literature on its use in clinical practice. A 2016 Cochrane review concluded that the available evidence at the time was insufficient to evaluate the effect of NIV on asthma exacerbations in children and that better designed studies with larger samples size are required.…”
Section: Discussionmentioning
confidence: 99%
“…They are also related to important healthcare expenses, roughly equivalent to two billion dollars a year in developed countries such as the United States. 1 A recently published study in Chile showed a significant increase in asthma hospitalization rates in 5---15year-old children, from 3.8 per 10,000 inhabitants in 2001 to 7.8 per 10,000 in 2014. 2 Most children hospitalized for asthma in Chile are younger than 12 years of age and almost 50% of them do not have an established diagnosis of asthma, and thus do not receive any controller treatment.…”
Section: Introductionmentioning
confidence: 98%